2019
DOI: 10.1002/jor.24335
|View full text |Cite
|
Sign up to set email alerts
|

Muscle and Joint Function After Anatomic and Reverse Total Shoulder Arthroplasty Using a Modular Shoulder Prosthesis

Abstract: Changes in joint architecture and muscle loading resulting from total shoulder arthroplasty (TSA) and reverse total shoulder arthroplasty (RSA) are known to influence joint stability and prosthesis survivorship. This study aimed to measure changes in muscle moment arms, muscle lines of action, as well as muscle and joint loading following TSA and RSA using a metal-backed uncemented modular shoulder prosthesis. Eight cadaveric upper extremities were assessed using a customized testing rig. Abduction, flexion, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 42 publications
(53 reference statements)
1
14
0
Order By: Relevance
“…Although in vitro experimental studies can provide valuable information regarding joint loading with ( Parsons et al, 2002 ; Dyrna et al, 2018 ) and without rotator cuff tears ( Ackland et al, 2019 ), the experimental cost is not conductive to parameter research. Musculoskeletal multibody dynamics modeling provides a non-invasive strong platform for understanding in vivo biomechanics of the shoulder and the effects of joint replacement on function.…”
Section: Introductionmentioning
confidence: 99%
“…Although in vitro experimental studies can provide valuable information regarding joint loading with ( Parsons et al, 2002 ; Dyrna et al, 2018 ) and without rotator cuff tears ( Ackland et al, 2019 ), the experimental cost is not conductive to parameter research. Musculoskeletal multibody dynamics modeling provides a non-invasive strong platform for understanding in vivo biomechanics of the shoulder and the effects of joint replacement on function.…”
Section: Introductionmentioning
confidence: 99%
“…Cadaveric studies have shown that implantation of a TSA can lead to lateralization of the glenohumeral joint center by 4.3 ± 3.2 mm 1 ; however, this is altered if asymmetrical reaming has to be performed for bone loss or severe retroversion in B2/B3 glenoids.…”
Section: Discussionmentioning
confidence: 99%
“…Minimizing joint lateralization intraoperatively may help to mitigate joint-contact stresses that are believed to contribute to accelerated polyethylene liner wear; however, further research is required to link joint force with component wear rates. 1 …”
Section: Discussionmentioning
confidence: 99%
“…Computational modeling of RTSA facilitates estimation of muscle and joint loading, which is currently impossible to measure non-invasively in vivo. Modeling and simulation of RTSA has played a critical role in guiding implant positioning and surgical technique [19][20][21][22], prosthesis selection [23,24], implant design [25,26], and post-operative rehabilitation prescription [27,28]. To date, most modeling and simulation tools require high levels of expertise and are generally restricted to the research setting.…”
Section: Computational Modeling Techniquesmentioning
confidence: 99%
“…For example, shoulder muscle forces during upper limb elevation can be calculated in several minutes using a subject-specific rigid body model (Figure 1A) [28,31]; however, since deformation mechanics is neglected, the internal stresses and strains in the bone and implant cannot be accurately evaluated using this method. An important utility of rigid body models has been in their capacity to estimate the influence of arthroplasty on muscle moment arms, muscle and joint forces, and range of motion (ROM) at the shoulder, which are primary indicators of implant functional performance [21,23,24,[29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Computational Modeling Techniquesmentioning
confidence: 99%